Cognitive functional therapy: an integrated behavioral approach for the targeted management of disabling low back pain (vol 98, pg 408, 2018) - O'Sullivan, P.; Caneiro, JP; O'Keeffe, M. (American Physical Therapy Association, 2018)
On page 420, a statement was incorrectly referenced. The statement with corrected reference is: “CFT has shown long-term superior efficacy to physical therapist–led exercise and manual therapy in a randomized trial.”63